The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.pestbp.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor (AhR) mediates resistance to apoptosis induced in breast cancer cells

Abstract: The aryl hydrocarbon receptor (AhR) is well known as a ligand binding transcription factor regulating various biological effects. Previously we have shown that long-term exposure to estrogen in breast cancer cells caused not only down regulation of estrogen receptor (ER) but also overexpression of AhR. The AhR interacts with several cell signaling pathways associated with induction of tyrosine kinases, cytokines and growth factors which may support the survival roles of AhR escaping from apoptosis elicited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 39 publications
3
63
0
2
Order By: Relevance
“…Interestingly, a recent meta-analysis found that exposure and increased blood levels of TCDD are significantly associated with the mortality caused by non-Hodgkin’s lymphoma (123). Furthermore, our previous reports strongly support the function of AhR to mediate an anti-apoptotic response in human lymphoma cells (124) and the vital role of RelB in AhR-mediated apoptotic resistance in human breast cancer cells (61, 66). Because both, AhRR and RelB, may form heterodimers with ARNT (figure 2), it is essential to understand the possible interaction of AhRR/ARNT with RelB and its consequences in regulation of cellular processes, like cell-cycling and apoptosis.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, a recent meta-analysis found that exposure and increased blood levels of TCDD are significantly associated with the mortality caused by non-Hodgkin’s lymphoma (123). Furthermore, our previous reports strongly support the function of AhR to mediate an anti-apoptotic response in human lymphoma cells (124) and the vital role of RelB in AhR-mediated apoptotic resistance in human breast cancer cells (61, 66). Because both, AhRR and RelB, may form heterodimers with ARNT (figure 2), it is essential to understand the possible interaction of AhRR/ARNT with RelB and its consequences in regulation of cellular processes, like cell-cycling and apoptosis.…”
Section: Resultssupporting
confidence: 74%
“…AhR is overexpressed and/or over-activated in various solid cancers (4143), in which it may drive proliferation, apoptosis resistance, extracellular matrix degradation, and immunosuppression (6066). Thus, AhR’s opponent may exhibit tumor-suppressive properties as depicted in figure 2.…”
Section: The Ahrr In Cancer Biologymentioning
confidence: 99%
“…In addition, recent studies from our laboratory and others have demonstrated the pivotal role of AhR/CYP1A1 in development of breast cancer. In that, it has been previously reported that TCDD, AhR ligand and potent CYP1A1 inducer, increased human breast cancer MCF-7 cell proliferation and the number and size of the mammospheres (CSC populations) [21] via the suppression of apoptosis [22]. In addition, Maayah et al, have demonstrated that inhibition of AhR/CYP1A1 pathway protects against breast cancer initiation and adduct formation in human epithelial breast MCF10A cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in work with rat intestinal epithelial cells the overexpression of cyclooxygenase 2, which is elevated in >80% of human colorectal adenocarcinomas, results in increased cellular adhesion and inhibition of apoptosis [34]. Similarly, increased expression of aryl hydrocarbon receptor can induce tumors and may contribute to apoptosis resistance to chemotherapeutic agents in breast cancer cells [35, 36]. Another growth factor, HER2, is overexpressed by 25 to 30 percent in some types of breast cancer cells [37].…”
Section: Physiochemical Barriers In Drug Deliverymentioning
confidence: 99%